2001
DOI: 10.1038/sj.onc.1204669
|View full text |Cite
|
Sign up to set email alerts
|

Acquired expression of transcriptionally active p73 in hepatocellular carcinoma cells

Abstract: p53 and p73 proteins activate similar target genes and induce apoptosis and cell cycle arrest. However, p53, but not p73 is considered a tumour-suppressor gene. Unlike p53, p73 de®ciency in mice does not lead to a cancerprone phenotype, and p73 gene is not mutated in human cancers, including hepatocellular carcinoma. Here we report that normal liver cells express only DN-p73 transcript forms giving rise to the synthesis of Nterminally truncated, transcriptionally inactive and dominant negative p73 proteins. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 33 publications
2
58
0
Order By: Relevance
“…The TP53 gene is mutated and mutant p53 protein is accumulated in at least 50% of cancers (Sigal and Rotter, 2000). On the other hand, the TP73 gene is very rarely mutated and overexpression of TAp73 is often observed in tumors (Zaika et al, 1999;Stiewe and Putzer, 2000;Sayan et al, 2001;Muller et al, 2005). The new transcriptionindependent function of p73 and p53 (Sayan et al, 2006) suggests new approaches to chemotherapy, which do not require transcriptionally active p53 family members.…”
Section: Discussionmentioning
confidence: 99%
“…The TP53 gene is mutated and mutant p53 protein is accumulated in at least 50% of cancers (Sigal and Rotter, 2000). On the other hand, the TP73 gene is very rarely mutated and overexpression of TAp73 is often observed in tumors (Zaika et al, 1999;Stiewe and Putzer, 2000;Sayan et al, 2001;Muller et al, 2005). The new transcriptionindependent function of p73 and p53 (Sayan et al, 2006) suggests new approaches to chemotherapy, which do not require transcriptionally active p53 family members.…”
Section: Discussionmentioning
confidence: 99%
“…14,22 However, detailed analysis of the p73 protein in tumor tissues has revealed that there are 2 p73 isoforms, DeltaTA-p73 and DeltaN- p73, which play opposing roles in carcinogenesis. [23][24][25][26][27] Very recently, Concin et al 28 reported that only the spliced DeltaTA-p73 transcripts from the TA promoter show significantly increased expression levels in the tumor, whereas the DeltaN-p73 transcript generated from the second promoter is not significantly up-regulated. Supporting evidence was also obtained from recently studies in vulval cancer and in hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The origins and culture conditions of HCC cell lines used here have been reported recently (Sayan et al, 2001a). HepG2 and SK-Hep1 cell line clones ectopically expressing mutant forms (p53-V143A, p53-R248W, p53-R249S) of p53 were generated by stable transfection with appropriate plasmids (Frebourg et al, 1992), as described previously (Ponchel et al, 1994).…”
Section: Cell Lines and Construction Of Stable Clonesmentioning
confidence: 99%
“…Detergent-soluble cell lysates were prepared and used for the analysis of total b-catenin and p53 protein levels by western blot assay, as described previously (Sayan et al, 2001a). Cytosolic and non-cytosolic forms of b-catenin were analysed on protein lysates prepared from corresponding cellular fractions.…”
Section: Preparation Of Cell Lysates and Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation